Auctions with Flexible Entry Fees - Maarten Janssen; Vladimir A. Karamychev; Emiel Maasland (Tinbergen Institute, 2009)
There is by now a large literature arguing that auctions with a variety of after-market interactions may not yield an efficient allocation of the objects for sale, especially when the bidders impose strong negative externalities upon each other. This paper argues that these inefficiencies can be avoided by asking bidders prior to the auction to submit any public payment they would like to make. These payments, so-called flexible entry fees, do not affect the allocation decision of the auctioneer. We show that auctions with flexible entry fees have a fully revealing equilibrium where bidders signal their type before the auction itself takes place.
Keywords: C72; D44; 330; auctions; efficiency; entry fee; negative externality; revenue; Auktionstheorie; Externer Effekt; Nichtkooperatives Spiel; Theorie